Economic implications of step-down outpatient management for fever and neutropenia episodes in pediatric cancer patients: a cost minimization analysis - Martha J. Avilés-Robles; Alfonso Reyes-López (BMC, 2024)
Abstract Background The management of febrile neutropenia (FN) in pediatric cancer patients has traditionally been conducted in a hospital setting. However, recent evidence has indicated that outpatient management of FN can be equally effective compared to inpatient care. Based on this evidence, we conducted a cost-minimization analysis (CMA) specifically focused on pediatric cancer patients in Mexico. Methods A piggy-back study was conducted during the execution of a non-inferiority clinical trial that compared outpatient treatment to inpatient treatment for FN in children with cancer. A CMA was performed from a societal perspective using patient-level data. In the previous study, we observed that step-down oral outpatient management of low-risk FN was as safe and effective as inpatient intravenous management. Direct and indirect costs were collected prospectively. The costs were adjusted for inflation and converted to US dollars, with values standardized to July 2022 costs. Statistical analysis using bootstrap methods was employed to obtain robust estimations for decision-making within the Mexican public health care system. Results A total of 117 FN episodes were analyzed, with 60 in the outpatient group and 57 in the inpatient group; however, complete cost data were available for only 115 FN episodes. The analysis revealed an average savings of $1,087 per FN episode managed on an outpatient basis, representing a significant 92% reduction in total cost per FN episode compared to inpatient treatment. Length of hospital stay and inpatient consultations emerged as the primary cost drivers within the inpatient care group. Conclusion This CMA demonstrates that the step-down outpatient management approach is cost-saving when compared to inpatient management of FN in pediatric cancer patients. The mean difference observed between the treatment groups provides support for decision-making within the public health care system, as outpatient management of FN allows for substantial cost savings without compromising patient health.